AN ANALYSIS OF JARGONS IN “MILANISTI NGALAM RAYA” COMMUNITY - IBRAHIM, FAHMI RACHMAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Jargon, Field, Mode, Tenor, Milanisti Ngalam Raya Community Nowadays, the use of language is extending. Language is not only for communication, but also for politics, advertisements, campaign, and some people also use the language to show their community identity. Sociolinguistics is the branch of linguistics which discusses the connection between languages and society. The relationship between languages and society is very interesting to investigate as the sociolinguistic analysis. Language is divided into some varieties. One of the varieties is jargons used in a community. In this study, there are two problems of the study: (1) What are jargons used by the members of Milanisti Ngalam Raya community; and (2) How isthe situational context aspects which consists of field, mode, and tenor applied in statements or conversations produced by the members of Milanisti Ngalam Raya community. Then, the objectives of the study are: (1) To find out the jargons used by the members of Milanisti Ngalam Raya community; and (2) To analyze the situational context aspects which consists of field, mode, and tenor applied in statements or conversations produced by the members of Milanisti Ngalam Raya community.This study used descriptive qualitative method because the object of this researchdeal with the exploration of human problem based on language phenomenon. Thepresent research design was content analysis concerning someone’s utterances. In this study, the data were collected from utterances in Milanisti Ngalam Raya community. This study describes the jargons phenomenon with the common meaning and particular meaning based on Dictionary and depth interview from the expert. This study also analyzes the jargon found based on aspects of situational context in jargon.There are sixteen of jargons used by the members in Milanisti Ngalam Raya community. Jargons have their own meaning for the members. Some jargons haveliteral meaning and jargon meaning, and some others do not. Based on the analysis,situational contexts which consist of field, mode, and tenor are important to see thebackground of the utterances. Situational contexts are influencing the use of wordliterally and specifically that the jargons used in the certain groups or society. Based on field, mode, and tenor, the writer can make a conclusion that jargons are important for the members to reach their purpose or the point of communication.The next study is suggested that they have to pay more attention to the timemanagement during the research to get the deeper information. Furthermore, the next researchers are suggested that they have to analyze the meaning of the jargons based on semantic and pragmatic theories.